Initial combination therapy with metformin plus colesevelam improves lipoprotein particles in patients with early type 2 diabetes mellitus (2012)
Background: The bile acid sequestrant colesevelam has been shown to significantly reduce low-density lipoprotein particle concentration (LDL-P) in adults with primary hyperlipidemia or type 2 diabetes mellitus (T2DM). Objective: To assess the effect of initial combination therapy with metformin plus colesevelam on lipoprotein particles in patients with T2DM (secondary efficacy variables). Methods: This 16-week, randomized, double-blind, placebo-controlled study enrolled drug-naïve adults with T2DM, glycated hemoglobin 6.5%-10.0%, low-density lipoprotein cholesterol (LDL-C) ?100 mg/dL, and triglycerides less than 500 mg/dL. Patients were randomized 1:1 to either open-label metformin (titrated to 1700 mg/day) plus double-blind colesevelam 3.75 g/day or open-label metformin plus double-blind placebo. Results: In total, 286 patients were randomized (metformin plus colesevelam [n = 145]; metformin plus placebo [n = 141]). Compared with metformin plus placebo, the combination of metformin plus colesevelam significantly reduced LDL-C (mean treatment difference: -16.3%), total cholesterol (-6.1%), non-high-density lipoprotein cholesterol (-8.3%), and apolipoprotein (apo) B (-8.0%) and significantly increased triglycerides (median treatment difference: 18.6%) and apoA-I (mean treatment difference: 4.4%; all P less than .001). Metformin plus colesevelam significantly reduced total LDL-P (mean treatment difference: absolute change -186 nmol/L [percent change -11.7%]; both P less than .0001), largely attributable to a reduction in small LDL-P, and increased total very-low-density lipoprotein particle concentration (mean treatment difference: absolute change 6 nmol/L; P =.03 [percent change 8.3%; P =.06]) and total high-density lipoprotein particle concentration (1.0 ?mol/L; P =.03 [4.5%; P =.01]) versus metformin plus placebo. Conclusion: Initial combination therapy with metformin plus colesevelam improved the atherogenic lipoprotein profile of patients with early T2DM by significantly reducing LDL-P. ClinicalTrials.gov identifier: NCT00570739. © 2012 National Lipid Association. All rights reserved.